A study on psychiatric illness in self-poisoning patients in a tertiary care hospital - Duraikannan, Amarnath; Anandhasekar, Monikeerthana (International Journal of Advances in Medicine, 2025)
Background: Self-poisoning, also known as self-ingestion or self-intoxication, refers to the deliberate ingestion of toxic substances with the intent of harming oneself. This study aimed to understand the close associations between self-poisoning patients and psychiatric illness, and to examine whether behaviour-based treatment was more effective than treatment as usual for people who harmed themselves. Methods: This retrospective study was conducted on 574 patients who were admitted with a history of self-poisoning in Thanjavur Medical College Hospital during the period of 1 year from 2015 to 2016. Patient history included age, sex, type of psychiatric illness, and type of poisoning consumed. A psychiatric diagnosis based on the ICD 10 was made by a psychiatrist once the clinical picture was clear. Results: Of 543 patients, 279 were female and 264 were male. A total of 184 (33.9%) patients consumed rat killer paste, 153 (28.2%) consumed OPC, 62 (11.4%) consumed ant killer powder, 38 (7%) consumed oleander, and 37 (6.8%) consumed tablets. Most patients had AD, ADS, AUD, IR, BPD, and acute psychosis for most poisons, such as ant killer powder poisoning, OPC, tablet poisoning, herbicide, kerosene, non-OPC, and rat killer paste poisoning. Conclusions: Implementing rigorous measures such as enforcing anti-dowry laws, promoting marriage counselling and women's empowerment, identifying and referring individuals with psychosocial issues for psychiatric support, and providing assistance to those with adjustment disorder could effectively reduce the incidence of poisoning and its associated mortality and morbidity rates.